The Physical Appearance and Depositional Environment of The Upper Damar Formation: Alertness from The Deep Pile Benchmark, Field Test, and Laboratory Data in Elucidating Land Subsidence Potential in Kendal-Semarang, Northern Coast of Central Java - Suyono, Suyono; Novianto, Muhammad Wafid Agung; Saputra, Sukahar Eka Adi; Wawan Hermawan, Wawan; Sollu, William (Geological Agency, 2025)
This paper examines the phenomenon land subsidence occurring in Kendal-Semarang, on the northern coast of Central Java Province (Java Island, Indonesia). Previous studies suggested that anthropogenic processes, particularly the over-exploration of groundwater, caused land subsidence in Kendal City and northern Semarang City. However, the geological factors such as sedimentology and stratigraphy below the Holocene deposit are possibly contributing to land subsidence in the Kendal-Semarang area remain unclear. This paper aims to analyze the stratigraphy, sedimentology, and insight into compaction and land subsidence potential of the basement Kendal-Semarang region within the Pliocene-Pleistocene Upper Damar Formation, based on measured sections in selected areas, analysis of deep pile benchmarks, and geotechnical aspects by using Standard Penetration Test (SPT) analysis. Specifically, it investigates the relationship between sediment loading and recent geological changes, related natural phenomena, erosion, and sedimentation, that may influence land stability. Detailed stratigraphic analyses were conducted in six selected locations through field measurements and borehole data to achieve this. These data were complemented by foraminifera and pollen analyses used to date the formation accurately. The stratigraphic interpretation suggests that during the Middle to Late Pliocene, the deposition environment of the Damar Formation transitioned from an upper delta plain to a tidal-influenced pro-delta environment. Two deep-pile benchmarks were also installed to monitor land movement, which revealed significant subsidence over one month, with rates of approximately 2.4 to 2.9 millim per month. These findings are supported by Standard Penetration Test (SPT) results, indicating that the underlying black and grey clay of the Upper Damar Formation-serving as the basement rock-exhibits N-SPT values between 5 and 27, ranging from firm to very stiff. Additionally, SEM analysis showed the prevalence of illite-smectite clay minerals, suggesting a moderate to high potential for compression and settlement under wet conditions. Understanding the compaction behaviour of these sediments helps explain ongoing land subsidence issues in the region, which is crucial for land use planning, infrastructure development, and hazard mitigation.